Differential Effects of Emotional Information on Interference Task Performance Across the Life Span - LaMonica, Haley M.; Keefe, Richard S.; Harvey, Philip D.; Gold, James M.; Goldberg, Terry E. (Frontiers in Aging Neuroscience, 2010)
While functioning in multiple domains declines with age, emotional regulation appears to remain preserved in older adults. The Emotion Inhibition (Emotional Stroop) Test requires participants to name the ink color in which neutrally- and emotionally-valenced words are printed. It was employed in the current investigation as a measure of affective regulation in the context of an interference task in relation to age. Results demonstrated that while participants ranging from 20 to 50 years of age performed significantly worse on the emotion Stroop Inhibition relative to the neutral Stroop Inhibition condition, subjects over 60 years of age displayed the converse of this pattern, performing better on the emotion than the neutral condition, suggesting that they are less affected by the emotional impact of the positive and negative words used in the former condition. This pattern of age-related change in the ability to manage emotion may be related to blunting of affective signaling in limbic structures or, at the psychological level, focusing on emotional regulation.